Information-signaling and competitive effects of foreign acquisitions in the US - Akhigbe, Aigbe; Martin, Anna D. (Journal of Banking & Finance, 2000)
The stock price effects for the domestic competitors of foreign acquisition targets in the US are found to be significantly positive. These results imply that signals of favorable industry conditions conveyed through cross-border acquisitions dominate any perceived changes in competitive balance. Consistent with the information-signaling hypothesis, the stock price effects are more favorable for relatively small competitors, for rivals with stock returns that are highly correlated with the target’s stock returns, when the targets experience favorable stock price effects, in technologically-intense industries, for rivals with poor prior performance, and with related acquisitions. Consistent with the competitive hypothesis, the stock price effects are less favorable with high degrees of financial leverage and when the acquirers already have a presence in the US.